2009
DOI: 10.1080/10641260802621791
|View full text |Cite
|
Sign up to set email alerts
|

Riverine and Reservoir Influences on Year Class Strength and Growth of Upper Great Plains Paddlefish

Abstract: A long-term investigation (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) was conducted on the relation between Yellowstone and Missouri River discharges, water level (elevation) changes of Lake Sakakawea, a Missouri River mainstem reservoir in western North Dakota, and the ecology of the Yellowstone-Sakakawea stock of paddlefish Polyodon spathula, a zooplanktivorous Acipenseriform fish. After impoundment in December 1953, Lake Sakakawea filled gradually over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Scarnecchia et al (2009) showed that both fish weight gain and GFB accumulation were greater in Yellowstone-Sakakawea stock paddlefish during years of higher reservoir levels and associated higher zooplankton abundance in the headwater region of Lake Sakakawea. Lower reservoir levels resulted in lower reservoir productivity, lower zooplankton density, smaller fish at age 9, and smaller GFBs in absolute weight and as a percentage of fish weight.…”
Section: Figure 10mentioning
confidence: 97%
See 2 more Smart Citations
“…Scarnecchia et al (2009) showed that both fish weight gain and GFB accumulation were greater in Yellowstone-Sakakawea stock paddlefish during years of higher reservoir levels and associated higher zooplankton abundance in the headwater region of Lake Sakakawea. Lower reservoir levels resulted in lower reservoir productivity, lower zooplankton density, smaller fish at age 9, and smaller GFBs in absolute weight and as a percentage of fish weight.…”
Section: Figure 10mentioning
confidence: 97%
“…However, strong year classes would have to become much more frequent than they are at present. As of 2010, the 1995 year class is dominating the population and the harvest (Scarnecchia et al, 2009), and recruitment of subsequent year classes is thought to be poor. For the Grand Lake stock, higher metabolic demands as the fish experience even warmer waters has the potential to push the species' life history flexibility to its limits, close to where the Gulf sturgeon now exists (Sulak and Randall, 2001).…”
Section: Paddlefish Life History and Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, repeated upsurge periods and subsequent population responses by remnant riverine fish are possible. Scarnecchia et al (2009) reported paddlefish populations increasing dramatically in response to the refilling of Lake Sakakawea on the Missouri River, almost 30 years after the initial filling phase.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, the impounded water of reservoirs can also provide benefits to remnant riverine fish species (Irz et al 2006;Ebner et al 2011;Lintermans 2012). Examples include paddlefish (Polyodon spathula) in the United States (Paukert and Fisher 2001;Scarnecchia et al 2009) and golden galaxias (Galaxias auratus) (Hardie et al 2007(Hardie et al , 2013 and Macquarie perch (Macquaria australasica) (Cadwallader 1981;Appleford et al 1998) in Australia.…”
Section: Introductionmentioning
confidence: 98%